THE ROLE OF ATYPICAL ANTIPSYCHOTIC DECREASING AGGRESIVENESS IN SCHIZOPHRENIA - Anggraini Maria, Juvita Novia (E-Jurnal Medika Udayana, 2013)
Schizophrenia is a psychiatry disorder accompanying by alteration of mind-set, perception,  thought, and behavior. Symptom of schizophrenia can be positive symptom and negative symptom. The positive symptom often became a fear for the others, that is aggresiveness as violance, suicide, ang homicide. Aggresiveness divided in five category, that is impulsivity, affective instability, anxiety/hyperarousal, cognitive disorganization, predatory/planned aggression. Pharmacology theraphy is a choice in decreasing aggresiveness in schizophrenia. Atypical antipsychotic theraphy indicate higher effectivity and fewer side effect than conventional antipsychotic.
Keywords: schizophrenia, aggresiveness, atypical antipsychotic.